House, Street, City: Le Corbusier’s Research Towards a New Urban Interior - Martinelli, Patrizio M. (Interiority, 2019)
Le Corbusier’s investigations, conducted between the 1910s and the 1930s, were focused on a new relationship between street and building. This research started from texts about the city, in particular, the writings of Eugène Hénard’s. These essays, dating back to 1903-1909, dealt with the necessity of a renewed strategy for the urban street, breaking down the monotony and the problems related to the sequence of buildings and creating a series of places as squares, gardens, and open courtyards: actual urban rooms between streets an buildings. Learning from those texts, Le Corbusier worked on a series of polemical writings about the rue corridor, collected in particular in The City of Tomorrow, Precisions and The Radiant City. A series of projects explored to the extreme consequences the topic: the Dom-ino building principle used for collective housing evolved to the redent, detached from the infrastructure, and the immeuble villa, with its inhabited façades. Finally, the curved redent for the Plan Obus in Algiers transformed the street itself into a "building as city" flowing in the landscape. The essay follows how Le Corbusier transforms the street and its traditional urban components in interior elements inside the buildings.